Perspectives of planning from the point of view of professional Family Health Strategy. - Polyana da Costa RIBEIRO; José Ivo dos Santos PEDROSA; Lídya Tolstenko NOGUEIRA; Maria Fátima de SOUSA (Universidade de Brasília, 2015)
The article looks at similarities and differences of the community diagnosis within the local planning of family health teams in Teresina. Was based on case study and focus group with teams belonging to the same territorial basis, involving hospital, health center of urban and rural area. Discusses three analytical dimensions: planning process, diagnosis in the planning of health teams and facilities/limits. It was evidenced that the planning is in its incipient, short-term, individualized and unsatisfactory demand needs. The interventions of the social actors have not involved sustainable actions, reflecting the verticality of the programmes and of distortions in the deployment process of the teams. Urge vigilance to managers with the organizational foundation of primary care, which is the diagnosis, in addition to implementing strategies for men's health, adolescent, bedridden and caregivers and collective education, neglected.